Analysis of Storyline Comparison in the Drama Script Amplop-amplop Laknat by Asmuddin and Penyesalan by Nora Adeliana: Comparative Studies - Alin Ambarwati; Seli Mauludani; Islam Ragab Abdelhamid Shehata (Journal of General Education and Humanities, 2025)
This research study aims to analyze the similarities and differences in the storyline in the drama scripts Amplop-amplop Laknat by Asmudin and Penyesalan by Nora Adeliana. This study uses a qualitative approach using the content analysis method with a network analysis technique that includes three components, namely: 1. data reduction; simplifying the drama script, 2. data presentation; conducting structural analysis of the drama script, and 3. withdrawal; drawing conclusions about the plot and presentation of the plot in the drama script using a comparative study. The data collection method is carried out using the literature observation technique. The collected data are analyzed using a structural study of the work's intrinsic elements to be studied more deeply using a comparative study of the storyline. The study results show that both drama scripts have similarities in terms of story ideas and differences in terms of the presentation of the storyline. The benefits of this study are that it will help gain a deep understanding of the structure of the script text and increase the knowledge of structural reviews in comparative studies on the plot and presentation of the plot of drama scripts.